Working with coaches and their teams in youth and collegiate sport in the USA: An interview with Dr Andy Gillham - Commentary - Vargas, T. M. (International Journal of Sports Science & Coaching, 2018)
The interview of Dr Andy Gillham öfters insights and recommendations to sport psychology consultants and to coaches, and the information discussed underscores the necessity for continued improvements in coaching education and the need for practical experience. Gillham's background in strength and conditioning and his personal experiences, combined with his PhD in sport psychology. allows for more comprehensive understanding of situations and provides discussion points and real-world examples that are very relevant today.